Analysis of the Institutional Transformation of the Russian Financial Market Control System by Creating a Mega-regulator - Nikonets, Olesya; Mandron, Victoria; Rulinskaya, Anna; Karavaeva, Yulia; Muravieva, Marina; Panina, Irina (International Journal of Economics and Financial Issues, 2016)
Increased competitive position of the financial market is one of the priority goals of national economic growth and clear-cut ascendancy of the state in the global economic space. The paper discusses one of the key problems of the financial market development and performance, namely, the policy of its regulating. This paper has also specified the stages of the financial market management system reformation, which allow to estimate the level of supervision integration for Russia over the period from 1991 to 2015. The study outcomes have showed that till the end of 2013 in Russia there was the sectoral supervision model, according to which the management was provided by areas of activity. The paper describes the system of the single regulatory authority functioning in the financial market as the improvement of its management policy. Moreover, the paper has determined the principles which are the basis of the mega-regulator performance such as independence, transparency, responsibility, collegiality, uniformity of the application. The advantages and the results of the financial mega-regulator performance were analyzed and powers of the Bank of Russia as a basic regulator of the financial market. Keywords: Financial market, management, control, financial mega-regulator JEL Classifications: G23, G32